Performance of Fixed Bed Column Study for The Removal of Nickel and Rhodamine B by Low Cost Hydroxyapatite/Alginate Composite Bead Adsorbent - Rosli, Mohd Arif; Wangit, Muhammad Azrin; Muhamad, Mimi Suliza (Progress in Engineering Application and Technology, 2020)
HAp/Alginate composite bead was tested in this research to identify its effectiveness on reducing the Ni2+ and RhB elements due to these substances are commonly discharged to the river in conjuction to various industrial activity occurred nowadays. The aim of this study is mainly to investigate and study the HAp/alginate composite media and to determine it’s performance in the dynamic system. Raw n-HAp powder and Alginate acid were used to develop the adsorbent bead and the method of Ni2+ and RhB adsorption is by applying fixed bed column technique. To study the effect of flow rate in percentage removal of Ni2+ and RhB, three different flow rate are studied where 5 mL/min, 10mL/min and 15 mL/min of flow rate were used. The dynamic modelling used in the continuous system are Thomas and Yoon-Nelson model. The best range of percentage removal of Ni2+ are between 99.5% and 40.5 % while for RhB the range of percentage removal are between 99.0 %. and 40.0 % using 5 mL/min of flow rate. The most effective flow rate to be utilize in the adsorption of Ni2+ and RhB is by using the lowest flow rate and based on the comparative study conducted in this study it ts proven that the Thomas and Yoon-Nelson model are fitted to be use. In further studies other metal ion parameter and dye based substances should be tested using this method and adsorbent.